Investigation to mitigate system-level factors contributing to hospital-acquired infection cases in the low-resource setting: A qualitative exploratory study in Bangladesh - Afsana Sultana; Fatema Tuz Johora; Palash Chandra Banik (PLoS ONE, 2026)
In Bangladesh, a low-resource setting country, the range of hospital-acquired infections (HAIs) is as high as 30% in some hospitals. Several studies have been conducted to determine the prevalence of HAIs and gaps in Infection Prevention and Control (IPC) measures. However, understanding the underlying causes and the barriers in the healthcare system that prevent the implementation of IPC measures and the control of HAIs has been the least explored. The study's primary aim was to comprehend the system-level factors influencing the high prevalence of hospital-acquired infections and the barriers to implementing strict, effective IPC measures in hospitals in Bangladesh. In this qualitative study, grounded theory with an inductive approach was adopted to understand the perspective of healthcare workers and key stakeholders regarding HAIs and IPC measures. Using a non-random, purposive sampling technique, we recruited participants from four major tertiary-care hospitals in Bangladesh. 10 KIIs (Directors, Deputy Directors, Nurse Supervisors and Superintendents) and one focus group discussion (six nurses). A semi-structured interview was conducted face-to-face with the participants. To ensure data reliability, methodological triangulation was conducted. For data analysis, the constant comparative method was adopted, which involved conceptualising and categorising through open coding. The study identified multiple factors, such as gaps in IPC knowledge and practice, a lack of HAI surveillance, resource constraints, hospital infrastructure, and overcrowding, as key barriers in implementing IPC measures effectively. To prevent HAIs, besides healthcare workers and hospital management, community awareness and adherence to IPC measures also play a key role. The findings show that, to prevent HAIs, besides the healthcare workers and hospital management, community awareness also plays a key role in implementing IPC measures successfully and preventing HAIs. This is why it is pertinent to develop IPC strategies that will engage both healthcare workers and the general population.